2009
DOI: 10.1074/jbc.m809509200
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the Thioredoxin Fold Superfamily Are Modulated by a Single Amino Acid Residue

Abstract: The ubiquitous thioredoxin fold proteins catalyze oxidation, reduction, or disulfide exchange reactions depending on their redox properties. They also play vital roles in protein folding, redox control, and disease. Here, we have shown that a single residue strongly modifies both the redox properties of thioredoxin fold proteins and their ability to interact with substrates. This residue is adjacent in three-dimensional space to the characteristic CXXC active site motif of thioredoxin fold proteins but distant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
115
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(128 citation statements)
references
References 55 publications
12
115
0
1
Order By: Relevance
“…21,36 The position of M88 HvTrxh2 is occupied by an isoleucine residue in EcTrx1 (Table 1), and a comprehensive mutational analysis, including determination of the structure of EcTrx1 I75T, demonstrated that this "cisPro minus 1 residue" is a general activity regulator of Trx fold proteins. 38 EcTrx1 I75P, however, was not generally more negatively affected than mutants with charged side chains (K, R, H, E, and D), and I75P had ∼10% residual activity toward insulin with either DTT or NTR as the reductant, which is similar to the results with HvTrxh2 M88P in the case of DTT but different from the results of the NTR recycling assay using DTNB as the final electron acceptor (Table 3). In the two different NTRindependent single-turnover BASI reduction assays, mutant M88P performed like A106P ( Figure S4 of the Supporting Information and Figure 7).…”
Section: ■ Discussionsupporting
confidence: 74%
“…21,36 The position of M88 HvTrxh2 is occupied by an isoleucine residue in EcTrx1 (Table 1), and a comprehensive mutational analysis, including determination of the structure of EcTrx1 I75T, demonstrated that this "cisPro minus 1 residue" is a general activity regulator of Trx fold proteins. 38 EcTrx1 I75P, however, was not generally more negatively affected than mutants with charged side chains (K, R, H, E, and D), and I75P had ∼10% residual activity toward insulin with either DTT or NTR as the reductant, which is similar to the results with HvTrxh2 M88P in the case of DTT but different from the results of the NTR recycling assay using DTNB as the final electron acceptor (Table 3). In the two different NTRindependent single-turnover BASI reduction assays, mutant M88P performed like A106P ( Figure S4 of the Supporting Information and Figure 7).…”
Section: ■ Discussionsupporting
confidence: 74%
“…This has also been shown in other studies where the XX dipeptide is changed (14,18 (Fig. 6), which has been shown to destabilize the oxidized form of the protein (14,17).…”
Section: Engineering a Denitrosylating Dsbgsupporting
confidence: 61%
“…This has also been shown in other studies where the XX dipeptide is changed (14,18 (Fig. 6), which has been shown to destabilize the oxidized form of the protein (14,17). The lack of this interaction from Met 200 in the DsbG CGPC-T200M mutant could lead to the observed stabilization of the oxidized form.…”
Section: Engineering a Denitrosylating Dsbgsupporting
confidence: 61%
See 2 more Smart Citations